Marketing Mix in Educational Services Marketing in the Digital Age - Moh Suhri Rohmansyah; Abdul Muin Bahaf; Anis Zohriah (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
In an era of technological dynamics and increasingly fierce competition, educational institutions are faced with the challenge of increasing the range of educational services. Marketing mix planning strategy is crucial in dealing with this change. The background to this issue reveals the need to understand the impact of marketing strategies on educational outreach amid an ever-changing environment. The purpose of this study is to find out what a marketing mix is, how the role of marketing mix in increasing the reach of educational services amid the dynamics of technological development, and to find out what are the main challenges in implementing a marketing mix planning strategy. This research uses a qualitative approach with a focus on literature review. Through a critical analysis of literature related to marketing mix planning in the marketing of educational services, this study aims to develop a solid theoretical foundation to understand the strategic role of marketing mix in the context of education. From the analysis of the literature review, the results of this study present an in-depth understanding of how marketing mix can affect the increase in the reach of educational services. The findings of this study provide insight into effective integration strategies, key challenges faced by educational institutions, and efforts to overcome these barriers. This research is expected to contribute new thinking in the context of marketing educational services, providing a foundation for the development of more effective and sustainable marketing strategies.